PENYULUHAN "HOW SAFE IS YOUR FOOD?" DI KOMUNITAS YAYASAN WORLD HARVEST, KARAWACI, TANGERANG [SEMINAR ON “HOW SAFE IS YOUR FOOD?” IN THE COMMUNITY OF WORLD HARVEST FOUNDATION, KARAWACI, TANGERANG] - Nuri Arum Anugrahati; Adolf Parhusip (Jurnal Sinergitas PKM & CSR, 2021)
Lack of public understanding about the importance of selection of food and good food processing is the background of the community services of Food Technology Department in Even Semester 2017/2018. The counseling entitled "How Safe is Your Food?" will be conducted in the parent community of World Harvest Foundation, Karawaci, Tangerang as a form of awareness of the Department of Food Technology to provide information about the source of the causes of frequent food poisoning, how to choose good food materials, and how to process food that considers hygiene and sanitation rule. The result showed most participants stated the counseling was useful for them although they have been implemented hygiene and sanitation rules in daily activities.BAHASA INDONESIA ABSTRACT: Kurangnya pemahaman masyarakat tentang pentingnya pemilihan bahan pangan dan cara pengolahan pangan yang baik melatarbelakangi pelaksanaan PkM Program Studi Teknologi Pangan di Semester Genap 2017/2018. Penyuluhan yang berjudul “How Safe is Your Food?” dilaksanakan pada komunitas di Yayasan World Harvest, Karawaci, Tangerang sebagai bentuk kepedulian Program Studi Teknologi Pangan untuk memberikan informasi tentang sumber penyebab keracunan pangan yang sering terjadi, cara memilih bahan pangan yang baik, dan cara mengolah pangan yang memperhatikan kaidah hygiene dan sanitasi. Walaupun sebagian besar peserta telah menerapkan kaidah hygiene dan sanitasi dalam mempersiapkan dan mengolah makanan sehari-hari namun hasil kuesioner menunjukkan 61% peserta yang hadir menyatakan penyuluhan berguna bagi peserta.